2022
DOI: 10.5430/jct.v11n1p101
|View full text |Cite
|
Sign up to set email alerts
|

Social Media as a Development Tool English Communicative Competence

Abstract: The purpose of the research is to determine the effectiveness of the practical application of social media based on Web 2.0 technologies, aimed at developing students' English-speaking communicative competence. To implement the tasks and test the hypothesis put forward, the following scientific research methods were used: empirical (experimental learning using social media based on Web 2.0); diagnostic: observation, testing of students; statistical method - mathematical analysis of the data obtained during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This finding demonstrates the motivating advantages of integrating technology and highlights students' increased excitement and dedication in English language learning environments. In seven studies, participants' speaking abilities improved (Puzanov et al, 2022;Bataineh et al, 2020;Ataeifar et al, 2019;Awada and Diab, 2018;Chagas and Pedro, 2021;Chiablaem, 2021). This finding indicates that using digital platforms and tools for speaking activities facilitates increased oral competency.…”
Section: Results Of the Studiesmentioning
confidence: 94%
“…This finding demonstrates the motivating advantages of integrating technology and highlights students' increased excitement and dedication in English language learning environments. In seven studies, participants' speaking abilities improved (Puzanov et al, 2022;Bataineh et al, 2020;Ataeifar et al, 2019;Awada and Diab, 2018;Chagas and Pedro, 2021;Chiablaem, 2021). This finding indicates that using digital platforms and tools for speaking activities facilitates increased oral competency.…”
Section: Results Of the Studiesmentioning
confidence: 94%
“…Firstly, TBL is an effective approach to raising students' English conversational skills, which is evident in plenty of studies (e.g., Bhandari, 2020;Nget et al, 2020;Nita et al, 2020;Anjum et al, 2019;Maghsoudi & Golshan, 2017;Campo, 2016). Secondly, the effectiveness of students' development of communicative English skills can be increased by using social media (Puzanov, Volynets, Lesiuk, Kharamurza, Vashyst, & Sadivnycha, 2022). Seilstad (2012) claimed that YouTube has fascinating materials and helps students learn English more productively by making the teaching content relevant and specific.…”
Section: Discussionmentioning
confidence: 99%
“…They also asserted that learners, in their study, perceive themselves to be more competent when they are using social media. Puzanov et al (2022) mentioned that well-known blogs, podcasting, media objects, wikis, and social bookmarks are the most popular social services that can be used effectively to develop learners’ communicative competence. They mentioned that interactivity in social media, such as Facebook, Instagram, and TikTok are helpful to foster learners’ communicative competence and their intention to communicate in a foreign language.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Earlier studies have indicated that social network, such as Telegram, Facebook, Youtube, and Instagram used in flipped classrooms can develop learners’ performance and active learning by paving the way for brainstorming activities (e.g., Nugroho and Atmojo, 2020 ; Tsai et al, 2020 ). Studies have shown that social media, with interesting platforms, inspire learners to interact with peers and teachers, which in turn, enhances learners’ intention to communicate in foreign language (e.g., Khajavy et al, 2016 ; Mohammadi et al, 2019 ; Puzanov et al, 2022 ). Some investigations also underscored the role of Telegram in inspiring learners to engage in learning tasks, and to promote their communicative competence ( Jafarigohar et al, 2019 ; Mohammadi et al, 2019 ).…”
Section: Suggestions For Further Researchmentioning
confidence: 99%